Understanding motivation for learning languages other than English: Life domains of L2 self. (June 2019) - Nakamura, Toshiyuki
Abstract: With the formation of a multilingual and multicultural world, there is a growing demand for second language (L2) motivation research, which has primarily focused on learners of English, for re-examining the theoretical frameworks to adequately explain motivation for learning languages other than English (LOTEs). This article responds to the call by introducing the concept of domain of L2 self . In doing so, it first investigates three developments in psychology, multilingualism, and linguistic philosophy: domain of possible selves (Oyserman & Markus, 1990 ), complementarity principle (Grosjean, 2010 ), and speech genres (Bakhtin, 1986 ). Through the analysis of interview data collected from two undergraduate Japanese language learners, it also explains how their ideal L2 selves (future self-images as competent L2 users), linked to particular life domains (e.g. interpersonal, leisure, education, career), developed through their learning of the domain-specific speech genres of the language. The conclusion suggests that especially in situations of LOTE learning, examining various domains of learners' ideal L2 selves, as well as speech genres used in the domains, would be beneficial for understanding their motivation to learn the target language as well as their bi/multilingual visions.